2014
DOI: 10.1653/024.097.0355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced-Risk Insecticides on Three Orchid Pests and Two Predacious Natural Enemies

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Although this method uses a small volume (~7.6 μL cm −2 leaf disc) of dsRNA solution compared to the floating leaf discs, it requires the manual spreading of dsRNA in order to cover an entire leaf surface. Alternatively, a surfactant such as Silwet L-77 can be used to promote liquid dispersion, but it has been shown to have a negative impact on some test organisms ( Cowles et al., 2000 ; Ray and Hoy, 2014 ; Abouelmaaty et al., 2019 ). Hence, identification of a high-throughput dsRNA delivery method to mites remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method uses a small volume (~7.6 μL cm −2 leaf disc) of dsRNA solution compared to the floating leaf discs, it requires the manual spreading of dsRNA in order to cover an entire leaf surface. Alternatively, a surfactant such as Silwet L-77 can be used to promote liquid dispersion, but it has been shown to have a negative impact on some test organisms ( Cowles et al., 2000 ; Ray and Hoy, 2014 ; Abouelmaaty et al., 2019 ). Hence, identification of a high-throughput dsRNA delivery method to mites remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The latter could be quite likely, given that many Chromobacterium species have larvicidal properties when fed live to mosquitoes (30). Interestingly, there is already a commercially available insecticide Grandevo (Marrone BioInovations), which was developed from a preparation of the bacterium Chromobacterium subtsugiae, that is used to target agricultural pest species (34,35). It is unclear whether Grandevo shares a mechanism of action with nonlive Csp_P powder.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember that similar biopesticides are already in use in the field. In the case of Grandevo, it has been demonstrated that toxicity does not occur ubiquitously in all arthropods that are exposed (34), indicating that Chromobacterium-based biopesticides may not be universally toxic among arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…We can find some studies from the past decade examining the synergistic effects of pesticides with surfactants. These studies have shown that such mixtures can be highly toxic not only for invertebrates but also vertebrates, including human cells (Cocco & Hoy, ; Mesnage et al, ; Peixoto, ; Ray & Hoy, ).…”
Section: Discussionmentioning
confidence: 99%